The role of new media tools in supporting health awareness for the protection of the Covaid 19 virus - Burhan Qadir, Adnan; Ahmad Najar, Sabah (Zanco Journal of Human Sciences, 2021)
The world has made big changes in the 21st century, and the main reason for this change is the advancement of technology, which is a skilled home and events are being moved very quickly, and so on. he has expanded his understanding and family and electronic relationships, and has accelerated his slow work in the area from moving them into homes and the only chickens in the coma The lga, therefore, has crossed the political and geographical boundaries of human activities, organisations and countries, and has delivered all kinds of services to humanbeings in all its forms, reconstructing the lives of individuals in a new way. To scientifically use social systems and their work on health awareness and in the new era and how to confront and protect themselves from the Covaid 19 virus, this research has been done and answers many questions that technology, especially social relations sites (SM), have created in the social system in general for this the attempts to investigate the data and damages have been made until we get a clear and open answer to the question. This research includes two main dimensions, the first being the new social media media, which is the main reason for the expansion of horizontal social relations between humans around the world, which finds itself in a large number of new media sites and tools, Which has become a very important factor in expanding these relations in these areas, health awareness, self-protection and self-protection of the Corona 19 virus, which is here The people answered many questions without answering their answers, and the research also tried to identify health awareness as a comedy of the singles and then find the role of social relations positions and new tools on health awareness. In the environment of the Kurdistan Region in general and the city of Erbil, the center of the research, because the capital of the Kurdistan Region and many international consulates and organizations are carrying out snakes and activities and have direct consequences with their country and places, which has led to the research documents that are the city of Erbil. Scientifically, this research goes into sociology and has its own importance: the importance of theory, which finds itself in finding a new model for measuring health awareness, and then the role of new media tools in making changes in health awareness, the second is practical importance that sees itself as the population of Erbil, which has been taken 3 levels (poor, medium and rich). They use new media tools and how much they have played a role in providing information and data special to the Corona virus (Coved 19 Virus). Reference: په‌رتووكه‌ كوردییه‌كان حه‌سه‌ن، سه‌عید، محه‌مه‌د، نازه‌نین عوسمان، نه‌هله‌ محمه‌د، فه‌ره‌یدون عه‌بدالستار، (2020)، رێنماییه‌كان بۆ خۆپاراستان له‌ كۆرۆنای تازه‌، زانكۆی سلێمانی كۆلێژی پزیشكی. زێباری، طاهر حسو، (2018)، ڕێبازەکانی توێژینەوەی زانستی، نوسینگەی تەفسیر، ‌‌أربیل. په‌رتووكه عه‌ره‌بییه‌كان‌ إسماعيل، محمود حسن، (1997)، التنشئة السياسية، دار النشر للجامعات، القاهرة. آل طويرش، موسى محمد، (2009)، الوعي السياسي كعنصر أساس في بناء النظام السياسي الديمقراطي، مجلة مركز المستنصرية للدراسات العربية والدولية، العدد 28. خلیل، د.محسین، (2006)، معجم علم اللجتماع المعاصر، دار الشروق، عمان. سکوت، جون، ترجمة: علي مولا، (2009)، علم الإجتماع المفاهيم الأساسية، الشبكة العربية للأبحاث والنشر، بيروت. عبدالجبار، حسين، (2008)، إتجاهات الاعلام الحديث والمعاصر، دار أسامة للنشر والتوزيع، عمان. غيث، محمد عاطف، (1990)، قاموس علم الاجتماع، الهيئة المصرية العامة للكتاب، القاهرة. مشري، مرسي، (2012)، شبكات التواصل الاجتماعي الرقمية، مجلة المستقبل العربي، بيروت، العدد ٣٩٥. په‌رتووكه بیانییه‌كان Alexa, (2019), pinterest.com Traffic Statistics, Alexa.com, accessed on 2019, Apr. 15, Aslam, Salman, (2019), YouTube by the Numbers: Stats, Demographics & Fun Facts, omnicore, accessed on 2019, Jan. 6, Bharatstudent, (2019), About bharatstudent, bharatstudent.com, accessed on 2019, Nov. 20. http://www.bharatstudent.com/help/about.php. Boyd, Danah m., (2008), Social Network Sites: Definition, History,and Scholarship, Journal of Computer-Mediated Communication, V.13, 2008, October 1. https://doi.org/10.1111/j.1083-6101.2007.00393.x. Fadhli, Mohd, (2018), A Case Study of Social Networking Site: Friendster vs Facebook, Malaysian Journal of Public Health Medicine, V. 18, 2018, August 30, https://www.danah.org/papers/JCMCIntro.pdf. Hosch, William L., (2019), Web 2.0, WaybackMachine, accessed on 2019, Oct 18, https://www.britannica.com/topic/Web-20. https://en.wikipedia.org/wiki/World_Health_Organization https://www.hawler.in/index.php/2017-12-28-23-20-20/item/25367-19 Kemp, Simon, (2019), Digital 2019: Global Internet use accelerates, We are social, accessed on 2019, Jan. 30, SnapInc, (2019), Snapchat, M APKMirror, accessed on 2019, Oct. 19, https://www.apkmirror.com/apk/snap-inc/snapchat/snapchat-10-70-5-0-release/. Thacker, D, (2019), Expediting changes to Google+, google, accessed on 2018, Dec. 10, https://www.blog.google/technology/safety- Wikipedia Inc, (2019), LinkedIn, Wikipedia.org, accessed on 2019, Nov. 10, https://en.wikipedia.org/wiki/LinkedIn. Wikipedia Inc, (2019), TikTok, Wikipedia.org, accessed on 2020, March 15, https://en.wikipedia.org/wiki/TikTok. Wikipedia Inc, (2019), Tumblr, Wikipedia.org, accessed on 2019, Nov. 11, https://en.wikipedia.org/wiki/Tumblr. World Health Organization. (2020). General's opening remarks at the media briefing on COVID-19 - 11 March 2020. Retrieved from General's opening remarks at the media briefing on COVID-19 - 11 March 2020.03. acs.edu.au.infotrecreation.and.fitness-what-ishealth.aspx" تێزەکانی دکتۆرا و نامەی ماستەرەکان: احمد، ئاراز رمضان، (2018)، ڕۆڵی پێگە ئەلکترۆنیەکان لە زانینی سیاسی لە هەرێمی کوردستاندا (لێکۆڵینەوەیەکی شیکاری و مەیدانیە لەسەر ڕۆڵی پێگە ئەلکترۆنیەکان لەسەر چاندنی زانینی سیاسی لە ناو جەماوەری دەستەبژێری کوردستان)، نامەی دكتۆرا، زانکۆی سه‌لاحه‌دین. باريان، احمد ريان. دور وسائل الاعلام في التثقيف الصحي للمراءة السعودية بمدينة الرياض سنة 1425 ه دراسة ميدانية رسالة الماجستر عير منشورة. حەمە ئەمین، ئەکرەم فەرەیدون، ڕۆڵی سۆشیاڵ میدیا لە خستنە ڕووی بیری سیاسی لای گەنجان، مجلة جامعة جيهان، العدد 1، اب 2018. عدد خاص بالمؤتمر العلمي الدولي الثاني لجامعة جيهان- اربيل في الاداب و الفنون، 27-28 حزيران / الغزال، مريم، (2014)، تأثیر مواقع التواصل الاجتماعي على تنمية الوعي السياسي، رسالة ماجستير، جامعة قاصدي مرباح، كلية الاعلام، ورقلة – الجزائر. محمد، دانا فاضل، (2015)، الآثار الاجتماعية والثقافية لاستخدام الإنترنيت على الشباب - دراسة ميدانية على عينة من الشباب في جامعة السليمانية، رسالة ماجستير، جامعة بيروت العربية، بيروت، لبنان. گۆڤار و بلاوكراوه‌كان (فلوس، مسعودە و تومی، الخنسا‌ء (2020)، الاعلام الجدید یهدد الصحة النفسیة داخل المجتمعات جرا‌ء جائحة فیروس كورونا، برلین، الدراسات الاعلامیة، مركز الدیمقراطیة العربیة، ألمانیا، العدد: 11. الامین، مرتضی البشیر عثمان و حمد، خالد عبد الحفیظ (2020)، وسائل التواصل الاجتماعي و تعزیز الوعي الصحي للوقایة من فایروس كورونا – صفحە الفیسبوك بالموقع الرسمي لوزراة الصحة السودانیة أنموذجا، برلین، مجلة الدراسات الاعلامیة، المركز الديمقراطي العربي، ألمانیا، العدد: